Increased Knowledge on Balanced Nutrition in Overcoming Wasting and Underweight and Monitoring the Nutritional Status of Groups of Children Under Five in Lestari Dadi Pegajahan Village - Panjaitan, Raini; Ginting, Joe Cresnando; Sitepu, Abdi Lestari; Octora, Debi Dinha (JURNAL PENGMAS KESTRA (JPK), 2024)
In Indonesia, the country faced a triple burden of malnutrition, including undernutrition, overnutrition, and micronutrient imbalances. The phenomena of wasting and underweight among toddlers were influenced by factors such as parental education, maternal knowledge, environmental conditions, health issues, awareness of nutrition, and the nutritional intake of toddlers. This activity aimed to improve knowledge about balanced nutrition to address wasting and underweight issues, as well as to monitor the nutritional status of toddlers in Lestari Dadi Pegajahan Village. The implementation method involved providing education on balanced nutrition to combat wasting and underweight, using health promotion media such as leaflets, PowerPoint presentations, and banners. Before the material presentation and leaflet distribution, participants completed a pretest about balanced nutrition and toddlers' nutritional status. After the education session, the nutritional status of toddlers was measured using a baby scale, weight scale, and microtoise. The measurement results were compared to the data from the previous month. Additionally, nutrition consultations were conducted with participants, and a posttest was administered at the end of the activity to measure changes in participants' knowledge. The posttest and pretest used the same set of 20 questions. The results showed an increase in the number of mothers with good knowledge, rising to 14 participants (70%) out of 20. Monitoring toddlers' nutritional status revealed 2 cases (10%) of underweight, 6 cases (30%) of wasting, and 12 cases (60%) of normal nutrition. In conclusion, this education activity successfully improved participants' knowledge, which they were able to apply in daily life.